Ramiro Pérez Reinoso: “Early Writings” (1918-1928) - Ahumada Infante, Aldo (2023)
The main objective of this work is to rescue the figure of Ramiro Perez Reinoso (1901-1994), Peruvian intellectual born in the “captive Arica”, but tacneño of roots, very little studied in spite of his relevance as historical figure as much for Peru as for Chile. For this case his first writings will be studied (1918 - 1928), where his initial ideological and theoretical influences will be analyzed, which will mutate as the decade of the twenties advances and with it all the historical evolution that awaited Peru, Tacna, Arica and his own life full of comings and goings between Chile and his native country. Specifically, we seek to analyze his first appreciations on the American thinkers of his time, his philosophical and political conceptions, and his epochal interpretation of the events occurring in post-war Peru.